Implementation of Sustainability Financial Accounting: Analysis of the Influence of ESG Performance on the Financial Performance of Public Companies in Indonesia - DEWI, Ni Made Santhi; PUTRI, Made Dea Yunika; INDRASWARI, Ni Putu Putri Gita; DEWI, Ni Kadek Ari Candra (Journal Management and Hospitality, 2024)
This study examines the implementation of sustainability accounting and its impact on the financial performance of public companies in Indonesia during 2020-2023. Using secondary data from 85 companies listed on the Indonesia Stock Exchange (IDX), this research analyzes the relationship between Environmental, Social, and Governance (ESG) performance and financial indicators through panel data regression analysis and Granger causality testing. Results show a significant positive correlation (r = 0.342, p < 0.01) between ESG scores and Return on Assets (ROA). The average ESG disclosure score increased from 48.6% in 2020 to 54.0% in 2023, while companies with high ESG ratings showed 59.6% higher ROA compared to low-rated peers. Granger causality testing confirms unidirectional causality from ESG performance to financial performance with a two-quarter lag. This study provides evidence that ESG investments generate an ROI of 374%, making sustainability accounting a strategic imperative rather than a mere compliance cost.